Sustainable chemical upcycling of waste polyolefins by heterogeneous catalysis. Issue 2 (15th April 2022) - Chu, Mingyu; Tu, Weilin; Yang, Shuangqiao; Zhang, Congyang; Li, Qingye; Zhang, Qiao; Chen, Jinxing
Abstract: The mass production of disposable polyolefin products has led to serious plastic pollution and an imbalance between manufacturing and recycling. Given these challenges, the chemical upcycling of waste polyolefins has attracted extensive attention due to its high efficiency and economic benefits. Herein, we review the development of polyolefin chemical upcycling in heterogeneous catalysis. The status quo of polyolefin recycling is first discussed. We then introduce the advanced strategies for chemical upcycling in the view of different value‐added products and discuss their challenges and prospects. Our in‐depth analysis centers on the catalytic mechanism and the design principle of heterogeneous catalysts. Finally, we outlook the promising directions to facilitate the degradation process via polymer and catalyst design and optimized catalytic engineering. Innovative strategies are expected to promote the chemical upcycling of polyolefins, bringing great promise for the sustainable development of society. Abstract : The chemical recycling of waste polyolefins has attracted extensive attention due to its high efficiency and economic benefits. This review summarizes the development of polyolefin chemical upcycling in heterogeneous catalysis and introduces advanced strategies in view of different value‐added products.